Peranan Koperasi Jasa Keuangan Syariah (KJKS) Amanah Mandiri Dalam Meningkatkan Minat Nasabah Terhadap Simpanan Wadi’ah Di Sekarputih Bagor Nganjuk - Juni Iswanto; Adi Marsono; Agus Thohawi (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2020)
Research on the aim of kanggo nyinaoni kanthi using the Amanah Mandiri kanggo sharia service cooperative (KJKS) adds a sense of joy to wadi savings marang. This research uses qualitative research. The research method of the Minangka research method is the research method of sing ana postpositivism, using the kanggo nyalonake babagan natural object, (minangka panemu experiment) where the researcher of the minangka acil is the result of an operational karo. Sharia financial institutions are present in the development of conventional financial institution practices and practices in the Japanese community. Sing diwenehake products by sharia banks may be conventional sing products polished kanthi nerangake contracts with sharia karo relationships. So that the iki thing is actually a negative thing for the public, the yen says sharia, maybe lipstick is just a sharia financial institution.